The Impact of Problem Based Learning with Tri Hita Karana on Scientific Literacy and Critical Thinking Skills - Nirmayani, L. Heny; Suastra, I Wayan (Universitas Pendidikan Ganesha, 2023)
Scientific literacy and critical thinking ability are two important things that determine students' success. Still, the two variables cannot be optimally owned by students. The research was carried out to analyze the impact of Tri Hita Karana's problem-based learning model on the Scientific literacy and critical thinking skills of PGSD students. The design of this study is quasi-experimental in the form of a nonequivalent post-test-only control group design. The sample of this study was 39 people consisting of 20 experimental class learners and 19 control class learners. Innovative learning models to improve Scientific literacy and critical thinking skills. Research data collection using test and questionnaire methods. The data analysis technique used in this study was manova with a result of 0.00 < 0.05. The results showed increased Scientific literacy and critical thinking skills after students were partially and simultaneously taught the Tri Hita Karana-based PBL Model. Judging from the mean score of each variable, the research results also show that the variable of critical thinking ability is more influenced than Scientific literacy, so it can be recommended as an innovative learning model to improve Scientific literacy and critical thinking skills.